2022
DOI: 10.1002/ijgo.14121
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in emergency versus electively scheduled cases of placenta accreta spectrum disorder managed by cesarean‐hysterectomy within a multidisciplinary care team

Abstract: Placenta accreta spectrum (PAS) includes varying combinations of abnormal placental implantation that may be accompanied by deficiency of uterine wall integrity. 1 A classification system by the International Federation of Gynecology and Obstetrics (FIGO) describes PAS disorders depending on the degree of uterine and parametrial invasion. 2 The risk of developing PAS disorders increases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Preterm birth is the common risk factor for perinatal morbidity and mortality shared by the majority of infants born via either approach of delivery in the context of abnormal placentation. [16–18,21–23,25–28,33] In our study, the gestational age at delivery was significantly lower in neonates born emergently compared to those with planned approaches. It mainly explains why the ECD group has lower birth weights and worse perinatal outcomes, because gestational age at delivery is a major determinant of neonatal survival and morbidity.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Preterm birth is the common risk factor for perinatal morbidity and mortality shared by the majority of infants born via either approach of delivery in the context of abnormal placentation. [16–18,21–23,25–28,33] In our study, the gestational age at delivery was significantly lower in neonates born emergently compared to those with planned approaches. It mainly explains why the ECD group has lower birth weights and worse perinatal outcomes, because gestational age at delivery is a major determinant of neonatal survival and morbidity.…”
Section: Discussionmentioning
confidence: 67%
“…Nine studies reported the means of gestational age at delivery in the PCD and ECD gro ups. [18][19][20][21][22]24,25,27,33] The overall pooled estimate for gestational age was significantly higher in the PCD group compared to the ECD group (SMD: 2.20; 95% CI: 1.25-3.15; P < .001; I 2 = 98%). This finding was also seen in the subgroups of women with PP alone (SMD: 1.29; 95% CI: 1.02-1.56; P < .001; I 2 = 22%) and PAS patients with or without coexistent PP (SMD: 2.51; 95% CI: 1.21-3.81; P < .001; I 2 = 98%) (Fig.…”
Section: Quantitative Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…There will, however, be some cases in which diagnoses are missed or are emergently managed with or without the presence of an experienced team. In such cases, outcomes have been shown to be poorer, highlighting the importance of optimizing diagnosis, pre-operative planning, and multidisciplinary care 21…”
Section: Multidisciplinary Management and Pre-operative Planningmentioning
confidence: 99%